2022
DOI: 10.1590/fst.55620
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic microencapsulation to enhance Bifidobacterium longum and Lactobacillus paracasei survival in goat cheese

Abstract: In the study, the microencapsulation method was applied in the production of white cheese from goat milk to prevent the loss of viability of Lactobacillus paracasei and Bifidobacterium longum due to environmental factors during their storage period.For this purpose, the cheese was obtained using three types of microcapsules -symbiotic microcapsules containing probiotic bacteria and probiotic + fructooligosaccharide, probiotic + inulin. In addition, probiotics, fructooligosaccharide and inulin have been added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Microencapsulation technology has been used for more than 50 years in food science disciplines, pharmaceutical areas, nutritional, and biological fields (Kavas et al, 2021). The microencapsulation process comprises the encapsulation of functional ingredients inside a shield-like protective coating material that acts as a barrier between the external environment and the probiotics inside the covering and creates particles in different sizes starting from very small sizes of nanometers to a few millimeters in diameters (Razavi et al, 2021).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Microencapsulation technology has been used for more than 50 years in food science disciplines, pharmaceutical areas, nutritional, and biological fields (Kavas et al, 2021). The microencapsulation process comprises the encapsulation of functional ingredients inside a shield-like protective coating material that acts as a barrier between the external environment and the probiotics inside the covering and creates particles in different sizes starting from very small sizes of nanometers to a few millimeters in diameters (Razavi et al, 2021).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…On the same line, Kavas et al (2021) [ 46 ] concluded insignificant changes in the sensory traits of goat cheese after 180 days of storage when L. lactis and B. longum encapsulated with alginate, fructooligosaccharide+ alginate, and inulin+ alginate separately. In a complementary line, the viability of L. paracasei and B. longum was preserved at a higher level in goat-cheese samples obtained with the addition of prebiotics to microcapsules throughout 180 days of storage at 4 °C [ 47 ].…”
Section: Food Probiotication With Microencapsulated Cellsmentioning
confidence: 99%
“…The extrusion microencapsulation method is an economical and simple method, does not require the use of chemical solvents, is minimally stressful for bacteria, and is, therefore, an effective microencapsulation technique in maintaining the viability of lactic acid bacteria in their passage through the Gastrointestinal system (Ahmed et al, 2021). Kavas et al (2022) investigated the changes in the numbers of Lactobacillus paracasei and Bifidobacterium longum in white goat cheese produced by adding free probiotic, prebiotic, and synbiotic microcapsules. They concluded that the viability of L. paracasei and B. longum was preserved with the microencapsulation technique, while the viability of probiotic bacteria was preserved at a higher level in cheese samples obtained by adding prebiotics to the microencapsules.…”
Section: Cheese May Provide Certain Advantages In Transporting Probio...mentioning
confidence: 99%